Beyond Work-Family Balance: Are Family-Friendly Organizations More Attractive? - Bourhis, Anne; Mekkaoui, Redouane (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 2010)
In a context of labour shortage, organizations face immense pressures to attract the best employees, and therefore deploy great efforts to increase their organizational attractiveness. In order to appeal to working women or younger workers, some organizations have implemented policies designed to balance work and family. Yet, the effect of such family-friendly practices (FFPs) on organizational attractiveness has seldom been investigated; this study endeavours to fill this gap.The literature review led us to posit that organizations that have implemented FFPs are more attractive to applicants (H1). However, this main effect may be moderated by desire for segmentation (H2). Role segmentation refers to the separation of personal and professional roles, while role integration designates the blurring of boundaries between roles. For example, individuals with a high level of desire for segmentation may be more attracted to companies that offer segmentation strategies (e.g., flexible scheduling) than to companies that offer integration practices (e.g., telecommuting). Finally, the effect of corporate reputation is also tested (H3).Using a policy-capturing research design, we tested the distinct effect of four FFPs (on-site child care; generous personal leaves; flexible scheduling; teleworking) on applicant attraction as well as the effects of organizational reputation and candidates’ desire for segmentation. Our results indicate that FFPs do have a main effect on attractiveness. More specifically, the two scenarios that received the highest scores on attractiveness were personal leaves and flexible scheduling. Contrary to expectations, we did not find a significant “Desire for segmentation x Family-friendly practices” interaction. However, the results reveal a significant three-way interaction, which indicates that the anticipated Desire for segmentation x Family-friendly practices is significant for some values of the reputation variable. As expected, corporate reputation does have a significant main effect on attractiveness. The implications of this study are discussed in conclusion.